2011
DOI: 10.1186/1477-7827-9-152
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the endocannabinoid system in viable and non-viable first trimester pregnancies by pregnancy-related hormones

Abstract: BackgroundIn early pregnancy, increased plasma levels of the endocannabinoid anandamide (AEA) are associated with miscarriage through mechanisms that might affect the developing placenta or maternal decidua.MethodsIn this study, we compare AEA levels in failed and viable pregnancies with the levels of the trophoblastic hormones (beta-human chorionic gonadotrophin (beta-hCG), progesterone (P4) and (pregnancy-associated placental protein-A (PAPP-A)) essential for early pregnancy success and relate that to the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 59 publications
(98 reference statements)
3
38
0
Order By: Relevance
“…The expression of NAPE-PLD was not significantly altered in the trophoblast, mesenchymal core or decidua of placentae from spontaneous miscarriage compared with that in placentae from elective surgical termination (Taylor et al 2011). Conversely, the expression of NAPE-PLD mRNA is at least twofold higher in the first-trimester (weeks 9-12) placentae from elective surgical termination than in those from spontaneous miscarriage ).…”
Section: Alterations In Endocannabinoid Signalling Promote Miscarriagmentioning
confidence: 78%
See 4 more Smart Citations
“…The expression of NAPE-PLD was not significantly altered in the trophoblast, mesenchymal core or decidua of placentae from spontaneous miscarriage compared with that in placentae from elective surgical termination (Taylor et al 2011). Conversely, the expression of NAPE-PLD mRNA is at least twofold higher in the first-trimester (weeks 9-12) placentae from elective surgical termination than in those from spontaneous miscarriage ).…”
Section: Alterations In Endocannabinoid Signalling Promote Miscarriagmentioning
confidence: 78%
“…This suggests that anandamide concentrations in the placenta are lower prior to spontaneous miscarriage. In direct contrast with these observations, several studies have found that plasma anandamide concentrations measured in the first trimester of women at risk of miscarriage are up to threefold higher in those who subsequently miscarried than in those who progressed to term (Habayeb et al 2004, Taylor et al 2011. A recent study, however, has failed to demonstrate a difference between plasma anandamide concentrations in women with normal pregnancies and those in women who subsequently miscarried (Tong et al 2012).…”
Section: Alterations In Endocannabinoid Signalling Promote Miscarriagmentioning
confidence: 90%
See 3 more Smart Citations